Bells of Rosarita - McDonald, Frank, 1899-1980; Townley, Jack, 1896-1960; Rogers, Roy, 1911-1998; Rogers, Dale Evans; Republic Pictures Corporation; Cinetel Films ([Los Angeles, CA] : Republic, 1945)
Roy plays himself--a Republic Western movie star who enlists his cowboy movie star friends to help Dale Evans keep the circus she inherited from her father.
Originally released as a motion picture in 1945.
Roy Rogers, Trigger, George "Gabby" Hayes, Dale Evans, Bob Nolan and the Sons of the Pioneers.
Cinematographer, Ernest Miller; editor, Arthur Roberts; musical director, Morton Scott; musical score, Joseph Dubin.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed December 4, 2015).
Keywords: Motion picture industry -- Drama; Circus -- Drama; Circus owners -- Drama; Circus performers -- Drama; Inheritance and succession -- Drama; Outlaws -- Drama; Western films; Feature films; Musical films; Internet videos; Streaming video